2014
DOI: 10.1134/s1063783414120282
|View full text |Cite
|
Sign up to set email alerts
|

Order-disorder structural phase transition in the system of intercalated Ni atoms in the Ni0.5TiSe2 compound

Abstract: Changes in the crystal structure of the Ni 0.5 TiSe 2 intercalated compound have been thoroughly investigated using powder X ray diffractometry in the temperature range from 93 to 700 K. It has been shown that upon heating to the temperature of about 400 K, this compound undergoes a phase transition from the monoclinic structure described by space group I12/m1 to the trigonal structure (P m1), which is associated with the disorder in the subsystem of intercalated Ni atoms. The supercooling effect with the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Table 2 provides the structural characteristics of the main phase Ni x TiSe 2 , as well as the cubic and hexagonal modifications of nickel selenide. According to Selezneva N.V. et al 22 the re-formation of the ordered phase requires a much longer time (12 hours) after heating above 400 °C. Although the exposure time at each temperature in our experiment was shorter, we observed the formation of NiSe 2 and NiSe in the temperature range of 300–500 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 provides the structural characteristics of the main phase Ni x TiSe 2 , as well as the cubic and hexagonal modifications of nickel selenide. According to Selezneva N.V. et al 22 the re-formation of the ordered phase requires a much longer time (12 hours) after heating above 400 °C. Although the exposure time at each temperature in our experiment was shorter, we observed the formation of NiSe 2 and NiSe in the temperature range of 300–500 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Heating Ni 0.5 TiSe 2 up to 117 1C causes the chains to become thermally unstable, resulting in the disordering of the Ni atoms. 22 Therefore, a thorough investigation of the crystal structure of the Ni 0.5 TiSe 2 compound between 25-1000 1C is necessary to determine the nature of Ni interaction with the host structure. This study investigates in situ the kinetics of the heating processes of Ni 0.5 TiSe 2 and experimentally determines the order parameter of the phase transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If necessary, the operations were repeated. This procedure has been successfully used in synthesis of other intercalated systems [5][6][7]. Its advantage is the more probable prevention of the formation of binary chalcogenides of both metals in case of direct synthesis from the initial elements.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, different concentrations of intercalated atoms in this compounds correspond to different structural modifications caused by a different number of T X 2 layers in a unit cell, as well as with ordering of vacancies and interstitial atoms in VDW gaps. Ordering in the intercalant sublattice, in addition to unit cell volume increase, is accompanied by a reduction of its symmetry [3][4][5]. Previous studies have shown that physical properties of compounds, obtained by intercalation with atoms of 3d-transition elements, differ significantly from the properties of initial T X 2 compounds.…”
Section: Introductionmentioning
confidence: 99%